Determination of the Low Pressure Zone of the Water Conducting Tract of Reservoirs - Negmatulloyev Zafardjon Turdibeko vich; Ganisher Abdurashidovich Nafasov; Saitmuratov Ulmasbek Nurullo ugli (Genius Journals, 2023)
In this article, it is obtained an exact solution to the problem of the flow of a dispersed mixtin e in a cylindrical pipe, and given the concentration distribution in the case of deposition of earned particles on the lower inner surface of the cylinder. The performed hydraulic calculations provided material for assessing the hydraulic operating conditions of the bends of the end section of the outlet, the nature of the occurrence of dynamic conditions in the flow and their effect on the flow structure. Based on the analysis of the operating conditions and the interaction of the flow with structural elements, the main sources and causes of vibration of the cone gates were identified.
Keywords: aeration process; cavitation; hydrostatic pressure